Learning by cutting. Public memory and the participatory approach at the Museum of Blacksmith Art and Cutlery - Altin, Roberta (Antropologia Pubblica, 2024)
This report concerns the Museum of Blacksmith Art and Cutlery in Maniago, which is embedded in the eco-museum network of the Western Dolomites. To engage local people and stakeholders in the process of local heritage, participatory methods have been adopted. The active engagement of women, youth, the visually impaired and other groups has stimulated self-awareness of the local community, creating an emotional and affective archive of the memory of their past work and connecting it to the new generation. The heritage of knives becomes a process constantly "under construction", and learning by cutting the stratified memories through the museum that is negotiating the common background to redefine the meaning of local identities.